A bibliometric analysis of the application of stem cells in glaucoma research from 1999 to 2022 - Tao, Yuanyuan; Zhang, Qian; Meng, Ming; Huang, Jufang (Frontiers in Cell and Developmental Biology, 2023)
Background: Glaucoma, a neurodegenerative disease of the retina, is the leading cause of irreversible blindness. Stem cells have therapeutic potential for glaucoma. However, few bibliometric studies have been published in this field. Concerning a visual map, this article aims to characterize the research context, cooperation relationship, hotspots, and trends concerning the application of stem cells in glaucoma research. Methods: Publications focusing on stem cell research and glaucoma were retrieved from the Web of Science Core Collection. VOSviewer, CiteSpace, Microsoft Excel, and Scimago Graphica were used to map the contributions of countries or regions, authors, organizations, and journals. Journal Impact Factor data were obtained from the Web of Science Core Collection. We analyzed the tendencies, hotspots, and knowledge networks using VOSviewer, and CiteSpace. Results: We analyzed 518 articles published from 1999 through 2022. In the first decade, the number of articles in this field increased slowly, and there was a marked acceleration in publication frequency after 2010. The USA, China, and England were the main contributors. Yiqin Du was the most prolific author, and among the top 10 prolific writers, Keith R. Martin’s work was cited most frequently. Investigative Ophthalmology & Visual Science, Experimental Eye Research, and Cornea published the most articles in this domain. The 3 most commonly co-cited journals were Investigative Ophthalmology & Visual Science, Experimental Eye Research, and Proceedings of the National Academy of Sciences of the United States of America. The Central South University, the University of Pittsburgh, and the National Institutes of Health National Eye Institute were highly prolific institutions in this research area. Our keywords analysis with VOSviewer suggested directions of future research and yielded the following recent key themes, extracellular vesicles, exosomes, mitochondria, growth factors, oxidative stress, and ocular diseases. 4 co-cited references had a citation burst duration until 2022. Conclusion: With improvements in overall quality of life and demographic transitions toward population aging, research and clinical focus on eye care has increased, with glaucoma as a key area of emphasis. This study added to our understanding of the global landscape and frontier hotspots in this field.